Trabalho, educação e juventude: contexto dos jovens do conjunto habitacional Terra Nossa em Francisco Beltrão/PR - Costa, Darciel Sinhori da (2023)
This dissertation was carried out within the scope of the Research Line Society, Knowledge and Education, of the Graduate Program in Education of the State University of Western Paraná, UNIOESTE, Francisco Beltrão Campus. The work intends to discuss the trajectories and experiences of young people, aged between eighteen and twenty-four years old, who graduated from high school and residents of the Terra Nossa housing complex, in terms of school life and insertion in the labor market, with the aim of highlighting the intersections of education and work categories and their implications in the context of that group. As specific objectives for this research, we outline understanding the social issue in brazil related to its historical constitution and changes in the world of work; characterize how the Terra Nossa housing complex was constituted and the socioeconomic profile of its young people; describe and analyze experiences in formal education, aiming to identify their particularities and categorize the crossings of experiences in the labor market and, consequently, their relationship with the school path. For this, we are guided by historical materialism, as a method and semi-structured interviews with eight young people. We could observe that two teaching networks coexist, aimed at framing young people for jobs according to ethnicity, social class, income and gender. The network aimed at children of the working class, aims at pragmatic training for the labor market, focused on the interests of new patterns of flexible accumulation and the precariousness of work relations today. We identified, as a historical particularity at the local level, the migratory movements that began in the thirties, whose expansion culminates in the socio-spatial and cultural segregation of disregarded groups, who end up fixing their homes in the peripheral areas of the municipality, forming neighborhoods with unique characteristics and potential. Which, however, are affected by social structures and institutions, which limit the conditions of existence of their residents, mainly regarding the experience of the juvenile condition of social moratorium. we conclude from the need to approach Francisco Beltrão peripheral youth with teaching aimed at overcoming the fragmented view between intellectual and manual work, in a polytechnic perspective, with a view to expanding the period of youth of these young people, in addition to the need to bring them closer to movements and organizations that aim to strengthen and improve their living conditions, public policies and social rights aimed at this public, considering their ethnic and cultural roots